NT PROBNP'S Prognostic Value Among Patients of Covid-19 without Heart Failure - Muhammad Asif, Muhammad Waqas, Hira Razzaq, Saud Javed Choudhry, Nahal Arshad, Nouman Nazeer, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: If Nt Pro BNP's prognostic value increased the mortality rate and hospitalization of covid-19 patients. Study Design: Retrospective study Place and Duration: Tehsil Headquarter Hospital Minchinabad. April 2021-Dec 2021. Methods: This research included 85 patients of both sexes with ages 18-65 years had coronavirus disease. After obtaining informed written permission, demographic data such as age, gender, height, weight, and place of residence were collected on all recruited participants. Comorbidities among all cases were assessed. NT proBNP> 88.64 pg/mL was considered as high and low was NT-proBNP≤88.64 pg/mL. Hospitalization and death rate among all cases were calculated. Results: There were 52 (61.2%) males and 33 (38.8%) females among all cases. The mean age of the enrolled cases was 55.7±17.76 years and had mean BMI 26.4±11.44 kg/m2. Hypertension was found in 35 (41.2%), chronic pulmonary disease in 20 (23.5%) cases, diabetes mellitus in 18 (21.2%) cases and 12 (14.1%) patients had chronic heart disease. Among 85 cases, 49 (57.6%) patients had high NT proBNP> 88.64 pg/mL and 36 (42.3%) patients had NT-proBNP≤88.64 pg/mL. We found higher level of CRP, creatinine and urea among patients of higher Nt ProBNP's value. Mortality in patients of higher Nt ProBNP's was found among 20 (40.8%) cases and no any death case found among patients of lower Nt ProBNP's value. Conclusion: We concluded in this study that increase in Nt ProBNP's value among patients of coronavirus cause higher number of deaths.